Entre traços e memórias: o Urban Sketchers e o registro da paisagem urbana de Feira de Santana - Mascarenhas, Ana Aparecida Porto (2025)
This study investigates the practice of Urban Sketchers and its relationship with memory and urban transformations, highlighting how in situ drawing contributes to the construction of both personal and collective narratives. Its objective is to analyze how the visual records I produced during the meetings of Urban Sketchers Feira de Santana reflect the changes in the city and the experiences of its inhabitants, highlighting the potential of drawing as an instrument for observing and interpreting the changing urban landscape. I adopt a qualitative approach, examining the drawings produced in these meetings to understand how they capture, record and reinterpret the city and its dynamics. To this end, I use a psychogeographic perspective, inspired by the practice of drifting, which allows for a sensitive exploration of urban spaces through the experience of walking and the act of drawing. The methodology includes direct observations, narratives, photographic records and the analysis of the drawings themselves, understanding them as visual documents that articulate memory, culture and urbanization. In this way, I propose that the practice of Urban Sketchers not only documents the city, but also establishes a dialogue between past and present, strengthening the affective ties of the inhabitants with spaces of historical, social and cultural relevance. Finally, I argue that this artistic practice plays an essential role in the valorization of urban memory, highlighting drawing as a form of cultural expression and visual record of the city of Feira de Santana - BA.